Non-Western Public Administration Model in Practice: Challenges and Sustainability Issues - Fathurrahman, Reza; Ferdiansyah, Julyan; Prasojo, Eko (Iapa Proceedings Conference, 2024)
The global mainstream has privileged western-based concepts to become an exclusive reference point that is considered applicable across countries. However, previous studies have found that the solely utilization of western-based theories is not enough to fully produce the expected output, particularly in Asian context. At this point, we argue that Non-Western approaches inspired by the Asian local culture may serve as a promising alternative to fill-in the gap. Nevertheless, only limited attempts have been done thus far to examine the sustainability of these alternatives and their position against the predominant western ideas. By using primary data collected from two special regions in Indonesia (Aceh and Yogyakarta), this study explores how the local values inspire an alternative administration model that is proven to be workable at practical level, and examines the challenges and its sustainability issues in the modern society. It is suggested that both accommodative attitude towards the co- existence of western and non-western public administration model in the region and the natural internal dynamics among societal actors have created a balanced system which ensures the sustainability of non-western public administration model.